Enhanced cell viability of hydroxyapatite nanowires by surfactant mediated synthesis and its growth mechanism. Issue 30 (7th March 2016) - Nathanael, A. Joseph; Hong, Sun Ig; Oh, Tae Hwan; Seo, Young Ho; Singh, Deepti; Han, Sung Soo
Abstract : Hydroxyapatite (HA) nanowires were synthesized using cetyl-trimethyl-ammonium-bromide (CTAB) as a surfactant and exhibited enhanced cell viability over other HA nanostructures. Abstract : Hydroxyapatite (HA) nanowires were grown by a simple hydrothermal method using cetyl-trimethyl-ammonium-bromide (CTAB) as a surfactant. The growth of preferentially oriented nanowires were suggested to be formed by the orientation-dependent electrostatic interaction between the CTAB ions and HA crystals. We prepared HA nanowires with a diameter of 30 ± 7 nm and the length of few micrometers. The prolonged hydrothermal treatment with the ideal concentration of CTAB induce the preferential growth of HA nanowires in the c -axis direction. The pronounced peak broadening of mainly (002) planes with the increase of the length of nanowires can be attributed to the natural bending of nanowires with an extremely high aspect ratio. The in vitro cell cultural studies of the HA nanowires showed that the osteoblast cell response enhanced with the uniformity and the specific surface area of HA nanowires.